The Effect of Single and Double-Doped Addition on 8YSZ Coating Layers Deposited on Inconel 625 by Electrophoretic Deposition - Aini, Kurotun; Amaliyah, Fina Fitratun; Sugiarti, Eni; Desiati, Resetiana Dwi; Latifah, Nurul; Ramandhany, Safitry; Fadilah, Ihah; Nasihah, Aunillah Putri El (National Research and Innovation Agency (BRIN), 2024)
The ceramic layers of 8 mol% yttria-stabilized zirconia (8YSZ), singly doped with Fe2O3 and doubly doped with Fe2O3 and Al2O3, have been deposited successfully on Inconel 625 substrates by the EPD (electrophoretic deposition) process. The oxide doping influenced the stability of the EPD suspension and affected the density of the resultant layer. In order to improve the adhesion between the layer and the substrate, a two-step sintering was performed up to 1200 ºC for a total duration of 4 hours in a horizontal vacuum furnace, with a heating rate of 2 ºC per minute in an Argon gas atmosphere. FE-SEM (field emission scanning electron microscopy) and vickers hardness tests were employed to investigate the effect of single and double doping on the morphology and hardness of the coating layers, respectively. EDS (energy dispersive spectroscopy) was employed to analyze the elemental composition of the layers, while XRD (x-ray diffractometry) was utilized to determine the crystalline phases. The results indicated that the double-doped coating sample possesses a better microstructure and the layer with double doping exhibits a denser microstructure and reduced porosity (3.84%) in contrast to the single doping layer (6.05%). The vickers hardness test indicates a rise in hardness from 65.3 HV with single doping to 283.78 HV with double-doping layers, due to the presence of Al2O3 as the interstitial agent, which reduces the layer's porosity and enhances adhesion between the layer and the substrate. Furthermore, the addition of Al2O3 as the double dopant may impede the tà m phase transformation, leading to enhanced thermal stability in the double-doped coating sample compared to the single-doped coating sample. This study shows that double doping techniques can improve the efficiency of ceramic coatings for high-temperature applications, such gas turbine components, and also giving opportunities for more research in oxidation, corrosion, and erosion testing.